HUBUNGAN ANTARA KOMUNIKASI IBU ANAK DENGAN KESIAPAN REMAJA PUTRI USIA 10-13 TAHUN DALAM MENGHADAPI MENSTRUASI PERTAMA (MENARCHE) DI MI BUSTANUL ULUM SASAP MOJOKERTO - Khalimatus Sa?diya, Lida; Mufidah, Kholiatin (JURNAL KEPERAWATAN SEHAT, 2016)
The female adolescent need sort of information about the process and the health during menstruation in order that there is no difficulty to face the first menstruation.The first information is from the mother, but she can not give the further information to the child since they couldn’t 0 well each other. This research is aimed to analize the correlation between the mother’s communication and the child by preparing the female adolescent from 10 to13 ages to face the first menstruation (Menarche) of MI Bustanul Ulum. The research design of analitic correlation uses cross sectional approach. The population is all female tenager from 10 to13 ages whom they never underwent Menarche are about 41 people which is used as Total Sampling. Analized used cross tabulation. The result showed that the better communication between the mother and the child, the move well-prepared the child facing menarche (61,5%). On the contrary, the worse communication between the mother and child, unwell-prepared the child facing menarche (82,1%). It means that there is correlation between the mother’s communication and the child by preparing the female adolescent from 10-13 ages to face the first menstruation (menarche) of MI Bustanul Ulum. It needs parents guidance for the female who will face the menarche.Keyword : Communication, preparation, Menarche